2015
DOI: 10.1155/2015/176261
|View full text |Cite
|
Sign up to set email alerts
|

Switching from Twice-Daily Basal Insulin Injections to Once-Daily Insulin Degludec Injection for Basal-Bolus Insulin Regimen in Japanese Patients with Type 1 Diabetes: A Pilot Study

Abstract: The aim of this study was to investigate the efficacy of insulin degludec used for basal-bolus insulin regimen after switching from twice-daily basal insulin in Japanese patients with type 1 diabetes mellitus. The subjects were 22 type 1 diabetes patients treated with basal-bolus insulin regimen with twice-daily basal insulin. Basal insulin was switched to once-daily injection of insulin degludec with 10% dose reduction. HbA1c and fasting plasma glucose (FPG) were measured before and 12 weeks after switching. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…Several previous studies have evaluated the changes in glycemic variability, measured by CGM, in DM1 patients who switched to IDeg. Three studies did not find significant changes in GV, or in 24-h analyses, or in nocturnal measurements [15] , [16] , [17] , compared with the study of Iga [18] where improvements in day-to-day variability measurements were observed, but not changes in MAGE or in J-index. In a cross-over study, where a 24 h analysis of CMG was performed, a statistically significant decrease in the standard deviation was observed for patients receiving IDeg, compared to those receiving Insulin Detemir twice a day [19] .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Several previous studies have evaluated the changes in glycemic variability, measured by CGM, in DM1 patients who switched to IDeg. Three studies did not find significant changes in GV, or in 24-h analyses, or in nocturnal measurements [15] , [16] , [17] , compared with the study of Iga [18] where improvements in day-to-day variability measurements were observed, but not changes in MAGE or in J-index. In a cross-over study, where a 24 h analysis of CMG was performed, a statistically significant decrease in the standard deviation was observed for patients receiving IDeg, compared to those receiving Insulin Detemir twice a day [19] .…”
Section: Discussionmentioning
confidence: 80%
“…Regarding glycemic control, previous studies in patients with DM1 have shown a minimum impact, which ranges from small reductions in A1c levels [15] , [24] , to an absence of changes [16] , [18] . Similar results were found when comparing IDeg to glargine in patients with DM2 who were insulin naïve [25] , [22] .…”
Section: Discussionmentioning
confidence: 95%
“…Degludec insulin has been reported to improve glucose control through a decrease in glycaemic variability and hypoglycaemic episodes and a decrease of insulin doses, notably in the maintenance period ( 14 , 16 , 32 ). In addition, a decrease in insulin requirement and an improvement of HbA1c has also been observed in patients switched from glargine to degludec, even though these results are still quite discordant ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 97%
“…32,38 In addition, the settings in which participants were monitored varied across studies, with some participants admitted in a hospital setting to control for the potential influence of diet and exercise, 27,32 while others were conducted in an ''outpatient'' setting. 39,[44][45][46] The majority of studies identified were also of short duration, with some studies being only 6-15 days long 27,32,47 and the majority being between 8 and 12 weeks long; this period of time will likely not enable sufficient data on hypoglycemia events to be captured to enable statistical comparisons and is not long enough to fully explore the efficacy and safety profile of basal insulins, particularly during the maintenance phase of treatment, where minimal dose adjustments are made. Further limitations of CGM studies identified in the present analysis included the small population sizes (with most direct comparison studies having fewer than 30 participants in each treatment arm), or with sample sizes being derived from subpopulations of larger RCTs, such as the BEGIN YOUNG study; thus these studies may have had insufficient statistical power to detect key outcomes.…”
Section: Cgm Data Comparing First-and Second-generation Basal Insulinmentioning
confidence: 99%